The influence of the direction of bilateral transfer on the acquisition and retention of gross motor dance movement sequences - Baard, Maryna L (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. in Human Movement Studies) -- University of Stellenbosch, 1988.